Evaluasi Obesitas Melalui Skrining Fat Caliper pada Populasi Usia Produktif di Kelurahan Grogol - Fenny Yunita; Alexander HalimSantoso; Farell ChristianGunaidi; Naufal Rayhan; Muhammad RifatUmarAlwini (Kusuma: Jurnal Pengabdian kepada Masyarakat, 2025)
Obesity and excessive body fat accumulation are major risk factors for various metabolic and cardiovascular diseases. Measuring subcutaneous fat thickness using a fat caliper is a simple, effective, and cost-effective method to assess body fat percentage in the productive age population. This community service activity was carried out in Grogol Village, West Jakarta, involving 67 productive age participants. Measurements were taken at four main body points, namely biceps, triceps, suprailiac, and subscapular, by a trained team from the Faculty of Medicine, Tarumanagara University. The screening results showed that in the fat caliper examination, the percentage of participants with high to very high categories in the biceps, triceps, suprailiac, and subscapular areas were 43.28%, 31.35%, 35.82%, and 8.95%, respectively, indicating a potential risk of excess body fat. Education on obesity prevention through healthy diet and increased physical activity was provided to the participants. This activity emphasizes the importance of early screening using fat calipers and health education as promotive and preventive measures to prevent obesity complications and improve the quality of life of the community.